"THE PLACE AND ROLE OF FLOWER PRODUCTION IN AGRICULTURE OF UZBEKISTAN" (Modern education and development, 2025)
Flower production occupies an important place in the structure of agriculture in Uzbekistan, playing a significant role in the country's economy, job creation and development of export potential. The article discusses the current state of floriculture in Uzbekistan, its economic significance, problems and development prospects. Particular attention is paid to the role of state support, the introduction of modern technologies and the expansion of export opportunities.